A study to find the correlation between ABO blood group and pulmonary tuberculosis - Dhanalakshmi, M N K; Dr. T Jaya Chandra (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Studies regarding pulmonary tuberculosis (PT) and blood group correlations were reported from different parts of globe. But there was huge disparity. Hence a study was conducted to find the relation between PT and ABO Rh blood group. Materials and Methods: Individuals with signs and symptoms suggestive of PT were included in the study. Two spot sputum samples were collected, sputum smears were stained by ZN staining. Simultaneously, ABO blood grouping and Rh typing was done for all the participants by slide agglutination test. P value of <0.05 was considered statistically significant. All the smear positive cases were included in test group. Results: During the study period, total 421 participants were included in the study the smear positivity was 64 (14.6%). In the test group, 2.2% were A+, 0.45% were A-; statistically there was no significant difference; 4.3% were B+, 0.9% were B- statistically there was no significant difference. Whereas 1.1% were AB+ and 0.45% were AB-; statistically there was no significant difference and 3.6% were O+, 1.4% were O-; statistically there was no significant difference. Conclusion: Present study showed that there was no significant association between blood groups and PT. Studies with large sample size for long time is recommended.